Double‐Layer MnCo2S4@Ni‐Co‐S Core/Shell Nanostructure on Nickel Foam for High‐Performance Supercapacitor. Issue 18 (27th June 2018) - Yu, Kun; Tang, Wing Man; Dai, Jiyan
Abstract : A double‐layer MnCo2 S4 @Ni‐Co‐S (MCS@NCS) core/shell nanocomposite is successfully deposited on nickel foam using a facile and simple method which includes a hydrothermal treatment and an electrochemical deposition and exhibits excellent electrochemical performance. With the introduction of sulfur via a sulfurization process, the MnCo2 S4 nanorods have larger specific surface area compared to the MnCo2 O4 nanorods and can serve as porous scaffolds for loading a large amount of additional active materials, facilitating electron transport and ion diffusion. The deposited Ni‐Co‐S nanosheet on MnCo2 S4 can further increase the electro‐active surface area and electrical conductivity as well as reinforce the mechanical stability of the whole electrode. Combining both structural and electrochemical advantages, the electrode with MCS@NCS heterostructures has high areal capacitance (10.14 F cm −2 at 1 mA cm −2 ). An asymmetric supercapacitor with Ni foam‐activated carbon as the negative electrode and Ni foam‐MCS@NCS as the positive electrode is fabricated and shows remarkable high areal capacitance (1.92 F cm −2 at 1 mA cm −2 ) and good cycling stability (72% capacitance retention after 5000 cycles), demonstrating its great potential as an efficient energy storage device for electronic systems. Abstract : A ternary metal sulphide Ni‐Co‐S nanosheet is grown on the surface of MnCo2 S4 by a simple electrochemical deposition to form a MnCo2 S4 @Ni‐Co‐S (MCS@NCS) core‐shell nanostructure. An asymmetric supercapacitor using Ni foam@MCS@NCS as the positive electrode and Ni foam@activated carbon as the negative electrode is fabricated and exhibits remarkable capacitance and durability, demonstrating its great potential for efficient energy storage.